The Influence Of Self-Efficacy And Time Management On The Work Readiness Of Students In The Office Administration Education Program Class Of 2022 - Dewi Amanda Nasution; Alfi Nura (CV Putra Publisher, 2026)
The purpose of this study is to determine the influence of self-efficacy and time management on the work readiness of students in the Office Administration Education Program, Class of 2022. The population in this study consists of all students in the Office Administration Education Study Program, Class of 2022. The sampling technique used in this study was total sampling, comprising 64 students. To collect data, the researcher used a questionnaire. The data analysis techniques used were multiple linear regression analysis, partial hypothesis testing (t-test), simultaneous hypothesis testing (F-test), and the coefficient of determination test (R²). The results of the study indicate that Self-Efficacy has a positive and significant effect on Work Readiness with a t-value of 7,041 and a significance level of 0,000. Time Management also has a positive and significant effect on Work Readiness with a t-value of 4,155 and a significance level of 0,000. Simultaneously, Self-Efficacy and Time Management have a positive and significant effect on Work Readiness with an F-value of 62,909 and a significance level of 0,000. The coefficient of determination (R²) value of 0,673 indicates that 67,3% of the variation in work readiness can be explained by self-efficacy and time management, while 32,7% is influenced by factors outside the scope of this study.